Paysage et système alimentaire à Curitiba (Brésil) : approche historique - Hervé Goulaze (Projets de Paysage)
Can the food found in a city provide information about the food systems that supply it? In the same way, can it express a relationship with existing or defunct food-producing landscapes? Based on the case of Curitiba (Brazil), we seek to understand the evolution of the food-producing landscapes linked to this city to understand how the food consumed there today can provide a synthesis of this evolution. The temporal division of ages inspired by Louis Malassis for qualifying the evolution of food systems made it possible to identify several periods each characterizing a different food system. They make it possible to bring together foods and moments in the history of the food-producing landscapes that supplied the capital of Paraná.